PENGARUH PEMBERIAN TOPIKAL ASI TERHADAP PELEPASAN TALI PUSAT BAYI BARU LAHIR DI PMB WILAYAH KERJA PUSKESMAS KASARANGAN - Nabella Faizah, Muthia; Kabuhung, Elvine Ivana; Mariana, Frani (Midwifery And Complementary Care, 2024)
Background: Umbilical cord care is the act of treating and tying the newborn's umbilical cord, to avoid infection, the umbilical cord is always cared for in a clean condition. One method of umbilical cord care is using breast milk. Topical breast milk treatment is very efficient because it costs nothing, is easy to apply and is a non-invasive technique, so it is safe to do. Objective: To determine the effect of topical breastfeeding on the release of the umbilical cord of newborns in PMB the working area of the Kasarangan Health Center. Methods: This study used a quasi-experimental with a post-test only with control group approach. The number of samples in this study were 20 respondents who were divided into 2 groups, namely 10 respondents in the intervention group and 10 respondents in the control group used consecutive sampling technique. The research instrument was in the form of respondent characteristics and observation sheets. Data analysis used the Mann Whitney test with a 95% level of confidence. Results: The duration of the release of the umbilical cord of newborns in the intervention group in the fast category was 7 babies (70%) and in the control group in the normal category there were 8 babies (80%). There was an effect of topical breastfeeding on the release of the umbilical cord of newborns in PMB the working area of the Kasarangan Health Center (p=0,028 <0,05). Conclusion: Topical administration of breast milk regularly (2x a day) can accelerate the release of the umbilical cord in newborns compared to non-routine (<2x a day). Keywords: newborn, umbilical cord, topical ASI.